THE EFFECT OF LEADERSHIP STYLE ON EMPLOYEE PERFORMANCE IN PURE PALM COOPERATIVE (Case Study: Tenggulun Village, Aceh Tamiang Regency) - Indriani Yunita Syahri (Institute of Computer Science (IOCS), 2020)
The purpose of this study was to describe employee performance, applied leadership style and to analyze the influence of leadership style on employee performance at Koperasi Sawit Murni in Tenggulun Village, Aceh Tamiang Regency. The analytical method used is descriptive analysis and multiple linear regression with SPSS tools. The results of the study concluded that the performance of the Koperasi Sawit Murni employees was in a poor category, because the employee's performance in completing tasks and daily work was not in accordance with the expectations of the leadership, the leadership style applied by the leadership of Pure Palm Oil Cooperative was democratic. The regression results show that it shows that employee performance is significantly influenced by a free, democratic and authoritarian leadership style.